2005
DOI: 10.1021/ja053336n
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of Fluorophore-Labeled DNA Oligonucleotides by Divalent Metal Ions:  Implications for Selection, Design, and Applications of Signaling Aptamers and Signaling Deoxyribozymes

Abstract: Recent years have seen a dramatic increase in the use of fluorescence-signaling DNA aptamers and deoxyribozymes as novel biosensing moieties. Many of these functional single-stranded DNA molecules are either engineered to function in the presence of divalent metal ion cofactors or designed as sensors for specific divalent metal ions. However, many divalent metal ions are potent fluorescence quenchers. In this study, we first set out to examine the factors that contribute to quenching of DNA-bound fluorophores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 81 publications
2
51
0
Order By: Relevance
“…Titration experiments using either 5=-32 P-BR10 or 5=P-BR14FD showed that the optimal ionic conditions for maximal activity of the WT enzyme were 10 mM MgCl 2 , similar to the value reported by Redko et al (6), or 400 M MnSO 4 (data not shown). Quenching of fluorescence by Mn 2ϩ or other transition metal ions is a well-known problem (26). To circumvent this in assays using 5=-P-BR14FD, 80 mM KCl was added to partially mask the backbone charge on the substrate, and divalent ion concentrations were set at 10 mM Mg 2ϩ Ϯ 0.1 mM Mn 2ϩ (i.e., a 100:1 ratio) despite the latter being suboptimal for Mn 2ϩ .…”
Section: Activity Of Rnase E With Different Metal Ionsmentioning
confidence: 99%
“…Titration experiments using either 5=-32 P-BR10 or 5=P-BR14FD showed that the optimal ionic conditions for maximal activity of the WT enzyme were 10 mM MgCl 2 , similar to the value reported by Redko et al (6), or 400 M MnSO 4 (data not shown). Quenching of fluorescence by Mn 2ϩ or other transition metal ions is a well-known problem (26). To circumvent this in assays using 5=-P-BR14FD, 80 mM KCl was added to partially mask the backbone charge on the substrate, and divalent ion concentrations were set at 10 mM Mg 2ϩ Ϯ 0.1 mM Mn 2ϩ (i.e., a 100:1 ratio) despite the latter being suboptimal for Mn 2ϩ .…”
Section: Activity Of Rnase E With Different Metal Ionsmentioning
confidence: 99%
“…FS1 was obtained from Keck Oligo Synthesis Facilities at Yale University, deprotected and purified by gel electrophoresis following a previously established protocol. [17][18][19][20][21][22][23][24] EC1, SS1 and LT1 were purchased from Integrated DNA Technologies and purified by gel electrophoresis. vortexing and place the tubes in -20 °C freezer for 30 min.…”
Section: Construction Of Rfd-ec1 and Rfss1 By Template Mediated Enzymmentioning
confidence: 99%
“…1) and investigated the use of RFDs as analytical tools. [17][18][19][20][21][22][23][24][25][26][27][28][29] RFDs catalyze the cleavage of a DNA-RNA chimeric substrate at a single ribonucleotide junction (R) that is flanked by a fluorophore (F) and a quencher (Q). The close proximity of F and Q renders the uncleaved substrate minimal fluorescence.…”
mentioning
confidence: 99%
“…[48,49] Briefly, a 3-piece DNA sandwich was first formed to bring a fluorophore-labeled DNA oligonucleotide (F-DNA) in close proximity to a quencher oligonucleotide (Q-DNA). In the presence of the target molecule, the unmodified oligonucleotide (MAP), which contains the target binding aptamer sequences, will fold to enable tight binding to its target (Fig.…”
Section: Aptasensing Platforms and Detection Assaysmentioning
confidence: 99%